Overwiew on molecular tools in bivalve shellfish aquaculture - Boudry, Pierre; Saavedra, Carlos (IVth EFARO Workshop Genetics tools for fisheries and aquaculture development, 2004)
Dr. Boudry presented an overview of the current development of molecular tools in shellfish bivalves, focussing on the recent development in oysters, species to which the most efforts are dedicated. This review was prepared together with Dr. Saavedra (Mollusc Research Group, Torre de la Sal, Spain) within the Fish and Shellfish group of the EU Network of Excellence "Marine Genomics Europe". Searches in DNA sequence databank ("GenBank") show that 4% are microsatellite sequences, 23% are mitochondrial sequences and the remaining 73 % other nuclear sequences. Among these, 75% concern oyster (Crassostrea) species, 15% mussel (Mytilus) species and 10% scallop (Argopecten) species. Some of these sequences were targeted as candidate genes related to known functions: immunity and disease resistance (i.e. antimicrobial peptides in mussels and oysters), byssus formation (foot adhesive proteins in mussel), digestive enzymes (amylases and cellulases in oysters), stress- and pollutant-induced genes (methalothioneins, HSP70s.), shell formation and development. For example, most genes coding for involved in the glucose pathway (Glucose transporter, Glycolysis, Glycogen metabolism and gluconeogenesis) in the Pacific oyster Crassostrea gigas are now characterized and can be monitored using real-time quantitative PCR. In addition to these targeted approaches, numerous cDNA libraries, of various tissues or differentially obtained by SSH, have been obtained for most species of interest. The most extensive EST characterization concerns the American oyster (Crassostrea virginica) with more than 4000 GenBank accessions. A database is especially dedicated to C. gigas hemocyte ESTs. Commonly, about 50% of the obtained ESTs cannot be related to known genes or functions. These EST libraries are use to develop new Real-time PCR assays, macro- and, more recently, micro-arrays. Studies concern environmental genomics (response to heavy metals and other pollutants), disease and stress resistance (summer mortality, pollutants.), mainly in oysters and mussels. An alternative and challenging approach in C. gigas has been developed based on MSSP technology (Massively Parallel Signature Sequencing by Lynk Therapeutics, CA, USA). Two BAC (Bacterial Artificial Chromosome) are now available for C. gigas and C. viriginica respectively. There are relatively little studies on proteome characterization (some work in mussel). Mitchondrial genome of bivalves has led to special attention due to its special mtDNA inheritance (Double Uniparental Inheritance) , demonstrated in mussels and clams. Complete mitochondrial genome sequences are available in mussel (male and female genomes), clam (male and female genomes) and oyster. Concerning complete nuclear genome sequencing, the "Oyster Genome Consortium" was constituted in 2003, joining 70 member laboratories from 10 contries and coordinated by Pr. Dennis Hedgecock. Following the recent rejection of the request to Dept of Energy Join Genome Institute (USA) to sequence C. gigas genome, the possibility to share this huge task between USA and Europe is currently discussed. Linkage maps are only available in oysters (2n = 20). In C. virginica, 282 markers (mostly AFLPs) are mapped, forming 12 linkage groups. In C. gigas, 100 microsatellite markers and more than 1000 AFLPs are mapped, forming 11 linkage groups. This map is currently used to map QTLs of growth outbreed families.